The dynamical evolution of protoplanetary discs and planets in dense star clusters - Flammini Dotti, Francesco; Capuzzo-Dolcetta, Roberto; Kouwenhoven, Thijs (Monthly notices of the Royal Astronomical Society, 2023)
Most stars are born in dense stellar environments, where the formation and early evolution of planetary systems may be significantly perturbed by encounters with neighbouring stars. To investigate the fate of circumstellar gas discs and planets around young stars dense stellar environments, we numerically evolve star-disc-planet systems. We use the N-body codes NBODY6++ GPU and SnIPES for the dynamical evolution of the stellar population, and the SPH-based code GaSPH for the dynamical evolution of protoplanetary discs. The secular evolution of a planetary system in a cluster differs from that of a field star. Most stellar encounters are tidal, adiabatic, and nearly-parabolic. The parameters that characterize the impact of an encounter include the orientation of the protoplanetary disc and planet relative to the orbit of the encountering star, and the orbital phase, and the semimajor axis of the planet. We investigate this dependence for close encounters (rp/a ≤ 100, where rp is the periastron distance of the encountering star and a is the semimajor axis of the planet). We also investigate distant perturbers (rp/a ≫ 100), which have a moderate effect on the dynamical evolution of the planet and the protoplanetary disc. We find that the evolution of protoplanetary discs in star clusters differs significantly from that of isolated systems. When interpreting the outcome of the planet formation process, it is thus important to consider their birth environments.
Vorab online veröffentlicht: 18. September 2023
Gesehen am 03.01.2024